Tears and their Role in Eye in Accordance with the Qur'ān and Medical Science - Munawar Hussain Chuhan,; Dr. Muhammad Sarfraz Khalid, (MEI, 2024)
Praise to Allah Blessing peace be upon our prophet Muhammad. All kinds of knowledge are important, but the most important science that contains the Glorious Qur'ān. According to this study, crying or shedding tears is the best approach to let go of unpleasant feelings like grief, anguish, and despair. It is occasionally also a means for people to express their happiness and satisfaction. In accordance with scientific perspectives, when tears are shed emotionally, levels of prolactin, manganese, potassium, and certain proteins are higher than when tears are just watering the eyes. Some fascinating new insights about crying are being provided by certain studies. The only animals who have evolved the capacity to cry when under emotional stress are humans. In accordance with Islamic perspectives, the Almighty Allah mentioned crying in the Holy Qur'ān as well. Tears and cries purify the soul of burden and grief as well as transgressions. It lets go of bad energy, and the tears wash away the dirt and injury.